2012
DOI: 10.1111/j.1945-5100.2012.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐lived radioactivity in the early solar system: The Super‐AGB star hypothesis

Abstract: Abstract-The composition of the most primitive solar system condensates, such as calciumaluminum-rich inclusions (CAIs) and micron-sized corundum grains, show that short-lived radionuclides (SLR), e.g., 26 Al, were present in the early solar system. Their abundances require a local or stellar origin, which, however, is far from being understood. We present for the first time the abundances of several SLR up to 60 Fe predicted from stars with initial mass in the range approximately 7-11 M x . These stars evolve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 115 publications
(229 reference statements)
1
39
0
Order By: Relevance
“…Different metallicities and larger grids of super-AGB models have started to populate the literature more recently (e.g. Siess 2006;Gil-Pons et al 2007;Poelarends et al 2008;Doherty et al 2010;Siess 2010;Ventura & D'Antona 2010;Lugaro et al 2012;Karakas et al 2012;Herwig et al 2012;Gil-Pons et al 2013;Ventura et al 2013;Jones et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Different metallicities and larger grids of super-AGB models have started to populate the literature more recently (e.g. Siess 2006;Gil-Pons et al 2007;Poelarends et al 2008;Doherty et al 2010;Siess 2010;Ventura & D'Antona 2010;Lugaro et al 2012;Karakas et al 2012;Herwig et al 2012;Gil-Pons et al 2013;Ventura et al 2013;Jones et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At low metallicity the elemnetal products of the sprocess nucleosynthesis in AGB stars can be directly observed in carbon-enhanced metal poor stars [4], [14], [15], [16], in post-AGB stars [17], [18] and in Ba stars [19]. For several cases the observations seem to agree well with theoretical model predictions [20], [21], while for other cases there are problems to reproduce the observations [22], [?…”
Section: Introductionmentioning
confidence: 99%
“…Ellis et al (1996) identified several possible target isotopes for such a study, including 60 Fe (see also Korschinek et al 1996), which is believed to be produced primarily in core-collapse and electroncapture SNe of massive stars, with mass M 8 M , via successive neutron capture on preexisting Fe isotopes, both before and during the explosion (Timmes et al 1995;Wanajo et al 2013). Other suggested sources are asymptotic giant branch (AGB; Busso et al 2003) and super-AGB (SAGB; Lugaro et al 2012) stars, as well as a rare class of high-density thermonuclear SNe (Woosley 1997).…”
Section: Introductionmentioning
confidence: 99%